PENGARUH FAKTOR FUNDAMENTAL MIKRO DAN MAKRO TERHADAP RETURN SAHAM (Studi pada Perusahaan Terdaftar Indeks Kompas-100 Periode Tahun 2013-2015) - Mawahib, Okky Aufarul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to explain whether micro and macro fundamental factors proxied by debt ratio, return on investment (ROI), earning per share (EPS), exchange rate, and interest rate influence stock return of the companies listed in Kompas100 index. Kompas100 index is considered attractive due to its tight liquidity and the capitalization which is about 70-80 % of the market capitalization. Total data were collected from 171 companies during the research period from 2013 to 2015. The secondary data was retrieved from Indonesia Capital Market Directory (ICMD) and Bank Indonesia (BI) monetary publication. The data were then analyzed by using Quantitative Methods i.e., multiple regression analysis based on SPSS software platform. The result of this research indicates that debt ratio and exchange rate positively and significantly influence stock return; however, the other variables like return on investment (ROI), earning per share (EPS), and interest rate do not have any significant effect on stock return for companies listed in Kompas100 index. Beside that the research indicates that simultaneously all of independent variables affecting stock return and the dominant effect is on exchange rate IDR to USD.Â Keywords: Stock Return, Micro Fundamental Factor, Macro Fundamental Factor, Debt Ratio, Return on Investment, Earning per Share, Exchange Rate and Interest Rate.